FORMULASI DAN EVALUASI MASKER GEL PEEL-OFF EKSTRAK ETANOL KULIT BUAH APEL (Phyrus mallus L) SEBAGAI ANTIOKSIDAN - A. Muflihunna; Sukmawati Syarif; A. Mumtihanah Mursyid (Universitas Islam Negeri Alauddin Makassar, 2019)
Antioxidants are substances that can fight the dangerous effects of free radicals or Reactive Oxygen Species (ROS) that are formed as a result of oxidative metabolism, which is the result of chemical reactions and metabolic processes that happen in the body. Antioxidant compounds can function as free radical scavengers, complex formers with metal antioxidants and function as reducing compounds. Peel-off mask is a cosmetic product that functions as a dead skin peel mechanically containing synthetic polymers that are quite safe and effective. The purpose of this study is to formulate and evaluate peel off gel masks from apple peel waste (Phyrus mallus L) as one of the stable free antiradicals. The peel off gel mask formulation was made through several stages, namely optimization, formulation and evaluation. This variation is done to optimize the effective base concentration to meet the criteria for the physical properties of the peel off mask pharmaceutically and can survive in shelf life through stability testing. The evaluation is based on physical parameters including organoleptic examination, homogeneity, viscosity measurement, determination of flow type,pH measurement, spreadability and drying time. The results of this study are apple peel extract can be formulated into peel off mask preparations with a PVA base of 2.5% and 5%. The peel off mask formulation of several variations of the PVA base concentration was concluded to be pharmaceutically stable based on the following parameters: In the pH test, PVA 2.5%=6.49; PVA 5%=6.47, In the dispersion test, the PVA spread value is 2.5%=6.7; PVA 5%=6.0, In the viscosity test, the value of PVA viscosity is 2.5%=28.27; PVA 5%=121.07.From all tests fulfilling the pharmacutics requirements and after the forced conditions did not experience significant changes